A method for preparing a semi-solid metal elastomer

The uniform semi-solid metal is prepared by ultrasonic and acidic solution bath and combined with the elastomer, which solves the problem that existing stretchable flexible conductors are difficult to maintain flexibility and stability when improving the conductivity, and achieves a semi-solid metal elastomer with high mechanical properties and high electrical conductivity.

CN119287203BActive Publication Date: 2025-04-29ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411829283.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-29
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

While improving the conductivity, existing stretchable flexible conductors are difficult to maintain the high flexibility and stability of the material, especially when liquid metal leakage is prone to occur during deformation.

Method used

The reaction between the liquid metal and the solid metal is strengthened by ultrasonic and acidic solution bath, uniform semisolid metal is prepared, and combined with the elastomer to form a semisolid metal elastomer.

Benefits of technology

The mechanical properties and conductivity of semi-solid metal elastomers have been improved, while the resistance changes are not obvious under strain, maintaining the high flexibility and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287203B_ABST
    Figure CN119287203B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a semi-solid metal elastomer, the method comprising: (1) adding liquid metal to water for ultrasonic mixing to obtain an aqueous solution of suspended particles of liquid metal droplets; (2) adding solid metal particles to the aqueous solution in step (1), ultrasonic mixing to obtain a mixed suspended aqueous solution of solid metal particles and liquid metal droplets; (3) adding an acidic solution to the mixed suspended aqueous solution in step (2) to obtain a solid precipitate, that is, a semi-solid metal SSM; (4) grinding the semi-solid metal and an elastomer precursor liquid, and curing to obtain a semi-solid metal elastomer SSME. The semi-solid metal elastomer prepared by the invention has better mechanical properties and electrical conductivity, and the resistance change under strain is not obvious.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flexible materials, and in particular to a method for preparing a semi-solid metal elastomer. Background Art

[0002] In the rapidly developing field of the intersection of electronic technology and materials science, stretchable flexible conductors are key components that connect rigid and flexible electronic devices, and the optimization of their performance has always been a hot topic and difficulty in research. Traditionally, such conductors usually rely on uniformly doping various conductive particles in a highly stretchable elastomer matrix to achieve a combination of conductive properties and mechanical flexibility. The choice of conductive particles is diverse, covering a variety of materials such as ions, metal particles, inorganic conductive particles, and conductive polymers. Among them, metal particles, due to their intrinsic high conductivity characteristics, show particularly outstanding advantages in the preparation of stretchable conductors, becoming the preferred filler for improving conductive properties.

[0003] However, stretchable conductors doped with metal particles have encountered an irreconcilable contradiction in practical applications. Specifically, when the doping amount of metal particles is at a low level, although the good stretchability of the elastomer can be maintained, the conductivity of the resulting conductor is significantly insufficient, and when strained by external force, the resistance value will rise sharply, severely limiting its application potential in dynamic or deformation environments. On the contrary, if the doping ratio of metal particles is greatly increased in order to improve conductivity, the physical properties of the elastomer matrix will change dramatically, which will be manifested as material embrittlement and a surge in modulus, which will greatly reduce the originally excellent stretchability and fail to meet the basic requirements of flexible electronic devices for material flexibility.

[0004] In response to the above difficulties, the industry has tried to introduce liquid metal fillers, such as gallium indium alloy (EGaIn), in order to improve the stretchability of the material by utilizing the fluidity of liquid metal while maintaining high conductivity. For example, the Chinese patent with publication number CN109467931A discloses a flexible dielectric elastomer composite material based on nano liquid metal, including an elastomer and a liquid metal, which is prepared by the following steps: preparing a thiol-coated nano liquid metal emulsion by ultrasonic crushing, dissolving the elastomer in a solvent, and then mixing and stirring the nano liquid metal emulsion to obtain a liquid metal / elastomer / solvent suspension, and forming a film by hot pressing or curing at room temperature to obtain the flexible dielectric elastomer composite material. However, this solution also faces severe challenges. Due to its strong fluidity and high surface tension, the EGaIn alloy is very easy to leak out of the elastomer matrix when the material is deformed, which not only leads to the interruption of the conductive path, but also may cause a short circuit failure inside the electronic device, seriously threatening the safe operation and stability of the equipment. For example, a method for preparing a liquid metal-based composite flexible conductive material disclosed in a Chinese patent with publication number CN117410030A provides a solution. A vacuum negative pressure environment is used to allow the organic solvent inside the thermoplastic elastomer to evaporate rapidly and actively degas during the curing process to form densely arranged micron-sized cavities, which can provide sufficient filling space for stress-fractured liquid metal nanoparticles and solve the problem of liquid metal leakage during the mechanical sintering process of the composite material.

[0005] Therefore, although the current technology has made some progress in the preparation of stretchable flexible conductors, there is still a lack of an ideal filler that can effectively improve the conductivity and ensure that the material maintains high flexibility and stability during deformation. Therefore, the development of new conductive fillers or composite material structures to solve this core contradiction in the existing technology has become the key to promoting the further development of stretchable flexible conductor technology. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a semi-solid metal elastomer, wherein the prepared semi-solid metal elastomer has better mechanical properties and electrical conductivity and the resistance change under strain is not obvious.

[0007] The present invention provides the following technical solutions:

[0008] A method for preparing a semi-solid metal elastomer, the preparation method comprising:

[0009] (1) adding liquid metal to water and mixing by ultrasonication to obtain an aqueous solution of suspended particles of liquid metal droplets;

[0010] (2) adding solid metal particles to the aqueous solution in step (1), and mixing by ultrasonication to obtain a mixed suspension aqueous solution of solid metal particles and liquid metal droplets;

[0011] (3) adding an acidic solution to the mixed suspension aqueous solution in step (2) to obtain a solid precipitate, i.e., a semi-solid metal SSM;

[0012] (4) The semi-solid metal and the elastomer precursor liquid are ground and solidified to obtain a semi-solid metal elastomer SSME.

[0013] The invention strengthens the metal-to-metal reaction between liquid metal and solid metal by ultrasound and acid solution bath, thereby preparing uniform semi-solid metal, and then compounding the semi-solid metal with elastomer to prepare semi-solid metal elastomer.

[0014] In step (1), the liquid metal is a liquid metal containing gallium atoms and having a melting point less than 30°C.

[0015] Preferably, the liquid metal is a gallium-indium alloy or a gallium-indium-tin alloy, and more preferably a gallium-indium alloy having a melting point of 16°C.

[0016] Specifically, in step (1), 1.2 parts by weight of liquid metal is added to a 50 ml centrifuge tube, and 15-100 parts by weight of water is added.

[0017] In step (2), the solid metal particles are selected from gold, silver, copper, iron, nickel or tin. Preferably, they are iron powder. The particle size of the particles can be 1 nm-5 μm, preferably 1 μm-3 μm.

[0018] In step (2), the mass ratio of the solid metal particles to the liquid metal is 0.2-1.0:1.2.

[0019] In step (3), the pH of the acidic solution is less than 5. For example, hydrochloric acid solution, sulfuric acid solution, nitric acid solution. Preferably, the concentration of the acidic solution is 35%. The amount of the acidic solution added is 0.1 mL-5 mL, preferably 1 mL.

[0020] In step (1) and step (2), the ultrasonic conditions are: 100-1000W, 20s-1h, preferably 500-800W and 1min-10min.

[0021] In step (4), the elastomer in the elastomer precursor solution is selected from polyacrylate elastomer, polyurethane elastomer, polyester elastomer, polyolefin elastomer, polyamide elastomer, natural rubber, synthetic rubber or silicone rubber.

[0022] The choice of elastomer will directly affect the final mechanical properties of the semi-solid metal elastomer. Various elastomers can be selected as semi-solid metal elastomers, for example, polyurethane elastomers, polyester elastomers, polyamide elastomers, polyolefin elastomers, polyacrylate elastomers, silicone rubber, natural rubber, nitrile rubber, butadiene rubber, etc.

[0023] Preferably, the polyurethane elastomer is a urea bond reinforced polyurethane elastomer, and the preparation method of the urea bond reinforced polyurethane elastomer is:

[0024] (A) dehydrating 10 to 15 parts by weight of polyester diol to obtain a dehydrated product; reacting the dehydrated product with 0.22 to 0.33 parts by weight of isofluorodione diisocyanate under an organotin catalyst condition;

[0025] (B) adding 0.9 to 1 parts by weight of a hydrazide compound and 40 to 80 parts by weight of N,N-methylformamide DMF to the reaction product of step (1) to continue the reaction to generate a u-TPU / DMF solution; wherein the hydrazide compound is represented by formula (I), formula (II) or formula (III);

[0026] .

[0027] In step (A), the polyester diol is preferably hydroxy-terminated poly(ε-caprolactone) with a molecular weight of 1000-3000; this is conducive to improving the viscosity of the polyurethane, thereby preparing a polyurethane elastomer with excellent performance. The reaction temperature is 60°C-90°C, preferably 75°C-80°C, and the reaction time is 2-5h, preferably 3h; this is conducive to improving the mechanical properties of the polyurethane.

[0028] In step (A), the dehydrated product is prepared by the following steps: 10-15 parts by weight of polyester diol and 0.03-0.06 parts by weight of catalyst are mixed, and dehydrated under reduced pressure at 120° C. to 140° C. for 1-3 hours to obtain a dehydrated product. The catalyst is an organic tin catalyst, preferably dibutyltin dilaurate. This is conducive to improving the degree of reaction.

[0029] In step (A), the amount of isophorone diisocyanate can be 2.2 to 3.3 parts by weight, preferably 2.2 to 2.5 parts by weight, which is beneficial to improving the viscosity and mechanical properties of the polyurethane.

[0030] In step (B), the hydrazide compound is selected from isophthaloyl hydrazide, phthaloyl hydrazide, terephthaloyl hydrazide, preferably isophthaloyl hydrazide. The amount of the hydrazide compound added can be 0.9 to 1 parts by weight, preferably 0.95 to 0.97 parts by weight.

[0031] In step (B), the reaction temperature is 20°C to 50°C, preferably 40°C to 45°C, and the reaction time is 8 to 24 hours, preferably 12 to 15 hours, which is conducive to improving the degree of reaction and increasing the mechanical properties of the polyurethane.

[0032] In step (4), the semi-solid metal content in the semi-solid metal elastomer SSME is 40-75 Vol%.

[0033] In step (4), an oven is used for thermal curing; the oven temperature is 50-100° C., preferably 70-80° C.; and the baking time is 1-5 hours, preferably 2-3 hours.

[0034] Compared with the prior art, the present invention has the following excellent effects:

[0035] In the preparation method of the semi-solid metal elastomer provided by the present invention, a semi-solid metal with extremely low hardness and modulus that does not flow can be prepared by ultrasound and acid solution bath, and the shape can be arbitrarily changed by hand kneading; and it has higher uniformity than the paste-like liquid metal prepared by the grinding method; the low modulus and variability of the semi-solid metal make it not affect the deformation of the polymer matrix when used as a conductive filler;

[0036] The semi-solid metal elastomer prepared by the present invention has better mechanical properties and electrical conductivity than the traditional rigid filler elastomer (doped with iron powder, silver powder, copper powder, carbon material, etc.);

[0037] When the semi-solid metal elastomer SSME prepared by the present invention is subjected to external forces (stretching, pressing, twisting, impact), the semi-solid metal inside can deform along with the deformation of the substrate, so that the SSME will not become brittle and the change of resistance with strain is very small.

[0038] In summary, the semi-solid metal obtained by the preparation method provided by the present invention is an ideal filler for conductive fillers, and the semi-solid metal elastomer prepared based on the semi-solid metal is a stretchable conductive material different from existing conductive elastomers, and has huge application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The appearance of the semi-solid metals prepared in Example 1 and Examples 4-6 and the appearance of the paste metal prepared by the grinding method in Comparative Example 1;

[0040] Figure 2 X-ray diffraction test patterns (XRD) of the semi-solid metal prepared in Example 1 and the paste metal prepared by the grinding method in Comparative Example 1;

[0041] Figure 3The image of the semi-solid metal prepared in Example 1 magnified 10,000 times under an electron microscope and the EDS spectrum analysis diagram;

[0042] Figure 4 This is an image of the paste prepared by the grinding method in Comparative Example 1, magnified 10,000 times under an electron microscope and an EDS spectrum analysis diagram;

[0043] Figure 5 A comparison chart of the Shore hardness of the semi-solid metal prepared in Example 1 and common materials;

[0044] Figure 6 A comparison chart of the modulus of the semi-solid metal prepared in Example 1 and common materials;

[0045] Figure 7 The semi-solid metal prepared in Example 1 is prepared into various shapes by hand kneading;

[0046] Figure 8 To compare the tensile properties of the semi-solid metal elastomer prepared in Example 1 with the semi-solid metal elastomers with different Fe contents prepared in Examples 5-6;

[0047] Fig. 9 To compare the tensile properties of the semi-solid metal prepared in Example 1 with the commercial SBS elastomer and the designed synthesized u-TPU in Example 7;

[0048] Fig.10 A comparison chart of the mechanical properties of a stretchable conductor prepared by doping the semi-solid metal prepared in Example 1 and the conventional rigid filler (Fe powder) in Comparative Example 3 into u-TPU;

[0049] Fig.11 An optical microscope image of the semi-solid metal filler inside the semi-solid metal elastomer prepared in Example 1 under tension;

[0050] Fig.12 The conductivity test result of the semi-solid metal elastomer prepared in Example 1 under tension;

[0051] Fig.13 This is the test result of the resistance change of the semi-solid metal elastomer prepared in Example 1 under tension. DETAILED DESCRIPTION

[0052] In the following Examples and Comparative Examples, "parts" refer to parts by weight unless otherwise stated.

[0053] The raw materials used in the embodiments and comparative examples are described below:

[0054] Gallium-indium alloy EGaIn (melting point 16 °C) was purchased from Dingguan Metal Company, iron powder was purchased from Zhongke Zhujin Nano New Materials, hydrochloric acid was purchased from Sinopharm Group, isophorone diisocyanate (IPDI), N,N-dimethylformamide (DMF), isophthalic acid hydrazide (ID) were purchased from Shanghai McLean. Polycaprolactone diol (PCL, Mn = 2000) was purchased from Tianjin Heowns Opde Technology Co., Ltd. Dibutyltin dilaurate (DBTDL) was purchased from TCI Shanghai. All chemicals were used as received without further purification.

[0055] Example 1

[0056] This embodiment provides a method for preparing a semi-solid metal elastomer, comprising the following steps:

[0057] (1) Pour 1.2 parts of EGaIn into a 50 ml centrifuge tube and add 15 ml of water. Place the tube under a probe sonicator and sonicate for 5 min (power 70%) to obtain an aqueous solution of suspended particles of liquid metal droplets.

[0058] (2) After the ultrasonic treatment is completed, add 0.4 parts of iron powder (spherical particles with a diameter of 3 microns) weighed in advance and continue ultrasonication for 5 minutes to mix evenly to obtain a mixed suspension aqueous solution of solid metal particles and liquid metal droplets;

[0059] (3) After mixing, add 1 ml of hydrochloric acid solution (pH <1) and stir for 5 min. Finally, pour off the upper solution and dry the obtained product in an oven at 70 °C for three hours to obtain a semi-solid metal (SSM).

[0060] (4) Add 10 parts of hydroxy-terminated poly(ε-caprolactone) (PCL, Mn=2000 g / mol) into a three-necked flask, heat to 140°C, remove water under reduced pressure for 3 hours, then cool to 80°C, add 2.33 parts of isofluorinated dione diisocyanate (IPDI) and 0.06 parts of dibutyltin dilaurate (DBTDL) to continue the reaction for 2 hours. After the reaction is completed, cool to 40°C, add 0.97 parts of isophthalic acid hydrazide (ID) as a chain extender, and add 60 parts of DMF again to continue the reaction for 10 hours. A u-TPU / DMF solution with a mass fraction of about 20% is obtained. The urea bond-reinforced polyurethane elastomer is prepared by pouring the solution into a mold and drying it in an oven at 70°C for more than 2 hours;

[0061] (5) Take 1.2 parts of the semi-solid metal prepared in step (3) and 1 part of the u-TPU / DMF solution prepared in step (4) and put them into an agate mortar and grind them thoroughly. Pour the ground mixture into a mold and place it in an oven at 70°C to dry for more than 3 hours to obtain a semi-solid metal elastomer (the volume ratio of semi-solid metal to polyurethane is 1:1), that is, SSME with a semi-solid metal content of 50 Vol%.

[0062] Example 2-3

[0063] The same method as in Example 1 was used to prepare SSME with semi-solid metal contents of 40 Vol% and 75 Vol%.

[0064] Embodiment 4-6

[0065] Semi-solid metals and SSMEs with Fe contents of 0.2 g, 0.6 g and 0.8 g were prepared in the same manner as in Example 1.

[0066] Example 7

[0067] The difference from Example 1 is that commercial SBS is used instead of urea bond reinforced polyurethane to prepare the semi-solid metal elastomer.

[0068] Comparative Example 1

[0069] The main difference from Example 1 is that the semi-solid metal is prepared by grinding: 1.2 parts of EGaIn are poured into an agate mortar, 0.4 parts of iron powder (spherical particles with a diameter of 3 μm) are added, and then fully ground for 5 minutes to obtain a flowable paste-like liquid metal.

[0070] Comparative Example 2

[0071] The only difference from Example 1 is that 1,4-butanediol (BDO) is used to replace isophthalic acid hydrazide. The process parameters are shown in Table 1.

[0072] Table 1 Process parameters of Example 1 and Comparative Example 2

[0073] .

[0074] Comparative Example 3

[0075] The difference from Example 1 is that Fe powder (spherical particles with a diameter of 3 μm) is used instead of semi-solid metal to prepare the stretchable conductor.

[0076] Comparative Example 4

[0077] The semi-solid SSME with a metal content of 25 Vol% was prepared in the same manner as in Example 1.

[0078] Test example

[0079] 1. Morphology and composition characterization

[0080] The semi-solid metals prepared in Example 1, Examples 4-6 and Comparative Example 1 were compared together, and the reaction degree of the gallium-indium alloy and the Fe powder was verified by XRD test, and the distribution of the Fe element was observed by EDS to analyze the uniformity of the semi-solid metal. They were respectively recorded as Implementation Sample 1, Implementation Samples 4-6, and Comparative Sample 1.

[0081] XRD test results are as follows Figure 1 and Figure 2 Shown by: Figure 1 It can be seen that the samples of implementation sample 1 and example samples 4-6 appear to be gray solids, while the sample of comparative sample 1 appears to be bright droplets, not solids. Taking implementation sample 1 as an example for further testing, the XRD test results ( Figure 2 ) shows that the sample 1 prepared by ultrasound produced more Fe 75 Ga 25 , which is the reaction product of Fe powder and EGaIn. The cavitation effect of ultrasound generates more and evenly distributed intermetallic compounds, resulting in a more solid product, which is beneficial for the preparation of stretchable conductors.

[0082] EDS test results are as follows Figure 3 and Figure 4 Shown: EDS of sample 1 ( Figure 3 ) shows that even after the sample is magnified 10,000 times, Fe can still be observed. Figure 4 ) showed that after the sample was magnified 10,000 times, no Fe element was observed, which indicates that the Fe element distribution of the sample prepared by ultrasound is more uniform.

[0083] 2. Hardness test

[0084] The semi-solid metal prepared in Example 1 was kneaded into a cylinder with a diameter of 1 cm and a height of 2 cm, and then the hardness of the semi-solid metal was tested using a Shore hardness tester; the test results are as follows: Figure 5 As shown: The Shore hardness of semi-solid metal is only 9, which is much lower than most materials, even lower than chewing gum.

[0085] 3. Modulus test

[0086] The semi-solid metal prepared in Example 1 was kneaded into a cylinder with a diameter of 1 cm and a height of 2 cm, and then a compression test was performed on the semi-solid metal using an electronic universal material testing machine. The compression modulus was calculated using a stress of 5% strain.

[0087] The test results are as follows Figure 6As shown: The modulus of semi-solid metal is only 35Kpa, which is close to the modulus of human skin and much lower than most synthetic materials. The softness of semi-solid metal allows it to be deformed into various shapes by hand (such as Figure 7 as shown).

[0088] 4. Tensile performance test

[0089] The urea bond reinforced polyurethane elastomer prepared in Example 1 and the polyurethane elastomer prepared in Comparative Example 2 were subjected to tensile tests using the following method: an electronic universal material testing machine (Instron 3343, sensor 50N) was used to conduct tensile tests on the specimens at a tensile speed of 100 m / min.

[0090] The test results are shown in Table 2: Compared with TPU prepared with isophthalic acid hydrazide, the mechanical properties of polyurethane prepared with butanediol are poor. This is because isophthalic acid hydrazide reacts with isocyanate to form urea bonds and amide groups, providing a large number of hydrogen bonds for the material, which is beneficial to improve the mechanical properties of polyurethane.

[0091] Table 2 Tensile properties test of the samples of Example 1 and Comparative Example 2

[0092] .

[0093] The same method was used to test the tensile properties of the samples of Example 1 and Examples 5-6.

[0094] The tensile test results are as follows Figure 8 As shown in the figure: For semi-solid metal elastomers prepared with different Fe contents, their tensile strength and elongation at break are basically the same. This is because despite the different Fe contents, they all have lower modulus and higher deformability, and can also conform to the deformation of the polymer matrix. Therefore, the mechanical properties are similar.

[0095] Table 3 Tensile properties test of the samples of Example 1 and Examples 5-6

[0096] ;

[0097] The same method was used to test the tensile properties of the samples in Example 1 and Example 7. The tensile test results are as follows: Fig. 9 As shown: when commercial SBS is used as the matrix, the tensile strength of the semi-solid metal elastomer is 1.36 MPa, the elongation at break is 665%, and it also has good mechanical properties; the semi-solid metal elastomer prepared with the u-TPU synthesized in Example 1 as the matrix has better tensile properties: the tensile strength is 7.43 MPa, and the elongation at break is 470%.

[0098] The mechanical properties of the polymer matrix have a great influence on the mechanical properties of the semi-solid metal elastomer. The urea bond reinforcement strategy of u-TPU greatly improves the tensile strength of the semi-solid metal elastomer.

[0099] Table 4 Tensile properties test of the samples of Example 1 and Example 7

[0100] ;

[0101] The same method was used to test the tensile properties of the samples of Example 1 and Comparative Example 3. The tensile test results are as follows: Fig.10 As shown: When a rigid filler (Fe powder as an example) is used as a conductive doping filler, the final tensile properties of the stretchable conductor are very poor, with a strength of 4.2Mpa and an elongation at break of only 138%, and the tensile curve shows inelastic behavior. When a semi-solid metal with the same fraction is used as a filler, the tensile curve is a typical elastic curve, with a tensile strength of 7.43Mpa and an elongation at break of 470%, which is much higher than the stretchable conductor prepared by Fe powder.

[0102] Table 5 Tensile properties test of the samples of Example 1 and Comparative Example 3

[0103] ;

[0104] Rigid fillers (such as Fe) often have very high modulus. When doped into a polymer matrix, they severely restrict the deformation of the matrix, thus causing the material modulus to increase and performance to deteriorate. However, due to their own low modulus and soft properties, when semi-solid metals are used as conductive fillers, the semi-solid metal units can deform along with the deformation of the matrix, thus not affecting the deformation of the polymer and allowing the material to maintain its elasticity as much as possible. This can be observed from the optical microscope image of the semi-solid metal elastomer ( Fig.11 ).

[0105] 5. Conductivity test

[0106] The conductivity of the semi-solid metal elastomer samples with different volume fractions in Examples 1-3 and Comparative Example 4 was tested by a four-probe conductivity tester:

[0107] Table 6 Conductivity test of SSME samples with different semi-solid metal contents

[0108] ;

[0109] The test results are shown in Table 6: The conductivity of SSME doped with semi-solid metals of different volume fractions was measured by a four-probe tester. When the volume fraction is 25 Vol%, due to the small amount of doping, no conductive path is formed inside the material, so the material is almost non-conductive (the conductivity is 2.079×10-7 S / m). When the volume fraction reaches 40 Vol%, the material begins to form a conductive path, and the conductivity jumps to 3460 S / m. When the volume fraction reaches 50 Vol% and 75 Vol%, the conductivity reaches 25430 S / m and 231300 S / m respectively, which is much higher than the stretchable conductor prepared by non-metal doping. Thanks to the deformability of the internally doped semi-solid metal ( Fig.10 ), the conductivity of SSME changes only slightly under strain ( Fig.12 ), with a strain of 400%, SSME still has a conductivity close to 10000 S / m (9210 S / m).

[0110] The resistance of SSME changes very little with stretching. When the strain is 400%, the resistance is only three times the initial resistance, which is much lower than the value predicted by Poillet theory ( Fig.13 ). Optical microscopy can prove the reason for this phenomenon ( Fig.10 ). As the matrix is ​​stretched, the shape of the semi-solid metal doped inside gradually changes from a sphere to an ellipsoid, so that when the matrix is ​​stretched and deformed greatly, the internal filler remains connected, thus ensuring the continuity of the conductive path.

[0111] This embodiment demonstrates a method for preparing a semi-solid metal and a semi-solid metal elastomer. The prepared semi-solid metal elastomer is a new type of stretchable conductor material with high mechanical properties, high electrical conductivity, and electrical conductivity strain insensitivity. It has a very broad application prospect in future wearable electronic devices.

Claims

1. A method for preparing a semi-solid metal elastomer, characterized in that: The preparation method comprises: (1) adding liquid metal to water and ultrasonically mixing to obtain an aqueous solution of suspended particles of liquid metal droplets; the liquid metal is a gallium-indium alloy or a gallium-indium-tin alloy; (2) adding solid metal particles to the aqueous solution in step (1), and mixing by ultrasonication to obtain a mixed suspension aqueous solution of solid metal particles and liquid metal droplets; (3) adding an acidic solution to the mixed suspension aqueous solution in step (2) to obtain a solid precipitate, i.e., a semi-solid metal SSM; (4) grinding the semi-solid metal and the elastomer precursor liquid, and solidifying to obtain a semi-solid metal elastomer SSME; In step (2), the mass ratio of the solid metal particles to the liquid metal is 0.2-1.0:1.2; In step (2), the solid metal particles are selected from gold, silver, copper, iron, nickel or tin; In step (4), the elastomer in the elastomer precursor solution is selected from a polyurethane elastomer, and the polyurethane elastomer is a urea bond-reinforced polyurethane elastomer. The preparation method of the urea bond-reinforced polyurethane elastomer is: (A) dehydrating 10 to 15 parts by weight of polyester diol to obtain a dehydrated product; reacting the dehydrated product with 0.22 to 0.33 parts by weight of isofluorodione diisocyanate under an organotin catalyst condition; (B) adding 0.9 to 1 parts by weight of a hydrazide compound and 40 to 80 parts by weight of N,N-methylformamide DMF to the reaction product of step (1) to continue the reaction to generate a u-TPU / DMF solution; wherein the hydrazide compound is represented by formula (I), formula (II) or formula (III); 。 2. The method for preparing a semi-solid metal elastomer according to claim 1, characterized in that: In step (3), the pH of the acidic solution is less than 5.

3. The method for preparing a semi-solid metal elastomer according to claim 1, characterized in that: In step (1) and step (2), the ultrasonic conditions are: 100-1000W, 20s-1h.

4. The method for preparing a semi-solid metal elastomer according to claim 1, characterized in that: In step (4), the content of SSM in the SSME is 40-75 Vol%.

Citation Information

Patent Citations

  • Flexible dielectric elastomer composite material based on nanometer liquid metal and preparation method thereof

    CN109467931A

  • Preparation method of liquid metal-based composite flexible conductive material

    CN117410030A

  • Method for doping micro nanoparticles into liquid metal and application of liquid metal-micro nanoparticle mixture

    CN108085519A

  • Liquid metal composite material and preparation method and application thereof

    CN118207461A